Ancient and early medieval Chinese literature : a reference guide. - Knechtges, David R.; Chang, Taiping (Handbuch der Orientalistik. China, 2013)
"The long-awaited, first Western-language reference guide, this work offers a wealth of information on writers, genres, literary schools and terms of the Chinese literary tradition from earliest times to the seventh century C.E."--